KASUS AGITASI AKIBAT PEMAKAIAN MEPHEDRONE - Astuti, Ni Made Widi; Kusuma Dewi, Dewa Ayu Sri; Sari, Pande Made Nova Armita; Wirasuta, IMA Gelgel (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 9 No 1 (2019): Indonesian Journal Of Legal And Forensic SciencesDO - 10.24843/IJLFS.2019.v09.i01.p06, 2019)
Mephedrone or 4-Methylmethcathinone is one type of NPS (New Psychoactive Substance) which is included in the katinon derivative. Mephedrone has been banned in Indonesia and in other countries such as the Netherlands. Mephedrone is used as a recrerational drug that can increase enthusiasm for its users. Misuse of mephedrone can cause toxicity to death for its users. In reviewing this article we will summarize the cases of mephedrone abuse in Indonesia, the pathway for mephedrone synthesis, the pharmacological, pharmacokinetic and pharmacodynamic effects of mephedrone and forensic toxicology analysis on cases of misuse of mephedrone compounds.